Long-chain noncoding RNA sequencing analysis reveals the molecular profiles of chemically induced mammary epithelial cells - Wei, Mengzhen; Tang, Wenkui; Lv, Danwei; Liu, Mingxing; Wang, Guodong; Liu, Quanhui; Qin, Liangshan; Huang, Ben; Zhang, Dandan (Frontiers in Genetics, 2023)
Previous studies from our group have demonstrated that small molecule compounds can induce goat ear fibroblasts to reprogram into mammary epithelial cells with lactation function. Long noncoding RNAs (lncRNAs) were important regulators affecting the cellular reprogramming process. In this study, we used lncRNA-Sequencing (lncRNA-seq) to analyze the lncRNA expression profile of cells before and after reprogramming (CK vs. 5i8 d). The results showed that a total of 3970 candidate differential lncRNAs were detected, 1170 annotated and 2800 new lncRNAs. Compared to 0 d cells, 738 lncRNAs were significantly upregulated and 550 were significantly downregulated in 8 d cells. Heat maps of lncrnas and target genes with significant differences showed that the fate of cell lineages changed. Functional enrichment analysis revealed that these differently expressed(DE) lncRNAs target genes were mainly involved in signaling pathways related to reprogramming and mammary gland development, such as the Wnt signaling pathway, PI3K-Akt signaling pathway, arginine and proline metabolism, ECM-receptor interaction, and MAPK signaling pathway. The accuracy of sequencing was verified by real-time fluorescence quantification (RT-qPCR) of lncRNAs and key candidate genes, and it was also demonstrated that the phenotype and genes of the cells were changed. Therefore, this study offers a foundation for explaining the molecular mechanisms of lncRNAs in chemically induced mammary epithelial cells.